Current Anti-angiogenic Therapies and Their Limitations - Mukherjee S.; Madamsetty V.S. (My University, 2025)
The process consist of angiogenesis presents the supply of blood to malignant cells promoting cancer development, invasion, and subsequent metastasis (Yoncheva and Momekov in Expert Opin Drug Deliv 8:1041–1056, 2011, [1]). The cancer cells live on high supply of blood and other nutrients. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.